Bits of Olive - Delgado, O.S. (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2011)
Before it happened, Allan had spend five excruciatingly long months attending the final details of his master piece; weird, one may think, since he had finished a fully praisable oil?clearly first-class?just twenty-three days after the first brush. Annabel, his daily muse and loveable companion, constantly emphasized the wholeness of the artwork and often commented on both, the artist and the picture, about each having in them particularities that rendered them unique, odd, and above all beautiful. But Allan relentlessly discharged her complements as they were, he thought, exceedingly influenced by the overwhelming seduction of her own features competently imprisoned in the canvas and, of course, the profound love between them.